2018
DOI: 10.1016/j.micres.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of murB-potABCD operon for polyamine uptake and peptidoglycan synthesis in Streptococcus suis

Abstract: Spermidine (Spd), spermine (Spm), and putrescine (Put), which are the most widely distributed cellular polyamines, are essential for normal growth and multiplication of both eukaryotic and prokaryotic cells. In this study, we identified the only putative polyamine transport system PotABCD in Streptococcus suis, a worldwide zoonotic Gram-positive pathogen causing lethal infections in humans and pigs. It was discovered that S. suis could uptake polyamines preferably Spd and Spm. By constructing a potA deleted mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 54 publications
1
30
1
1
Order By: Relevance
“…Remarkably, the four plasmid-complemented mutants displayed stronger autoaggregation than that observed with 12/111, along with frequent cell heterogeneity and abnormal septation. In S. suis, long chains with abnormal septation have been associated with unstable peptidoglycan due to the deletion of potA, a major part of the potABCD polyamine transporter [ 80 ]. SAM is a key determinant of the synthesis of AI-2 and of polyamines [ 64 , 65 ], i.e., molecules which play a role in peptidoglycan synthesis in Streptococci [ 80 , 81 ] and in biofilm formation [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the four plasmid-complemented mutants displayed stronger autoaggregation than that observed with 12/111, along with frequent cell heterogeneity and abnormal septation. In S. suis, long chains with abnormal septation have been associated with unstable peptidoglycan due to the deletion of potA, a major part of the potABCD polyamine transporter [ 80 ]. SAM is a key determinant of the synthesis of AI-2 and of polyamines [ 64 , 65 ], i.e., molecules which play a role in peptidoglycan synthesis in Streptococci [ 80 , 81 ] and in biofilm formation [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…In S. suis, long chains with abnormal septation have been associated with unstable peptidoglycan due to the deletion of potA, a major part of the potABCD polyamine transporter [ 80 ]. SAM is a key determinant of the synthesis of AI-2 and of polyamines [ 64 , 65 ], i.e., molecules which play a role in peptidoglycan synthesis in Streptococci [ 80 , 81 ] and in biofilm formation [ 82 , 83 ]. Thus, we suggest that (1) the stronger autoaggregation and higher cell heterogeneity with abnormal septation observed in our study with the plasmid-complemented strains may have resulted from increased synthesis of AI-2 and polyamines due to the overexpression of metK carried on the plasmids, and (2) metK may play a role in quorum sensing and peptidoglycan synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review has demonstrated the presence of different types of vesicles released from both Gram-negative and Gram-positive bacteria, indicating also that the composition of the cell membrane plays a role in vesiculation (Toyofuku et al, 2019). The presence of a thickened peptidoglycan cell wall in Gram-positive bacteria restricts the penetration of most drugs into the cells, which suggests the need of an alternative receptor-mediated transport system (Liu et al, 2018). However, the high lipid content of the Gram-negative cell membrane with a thin layer of peptidoglycan increases membrane fluidity thus facilitating OMV release (Roier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are ubiquitous in eukaryotic and prokaryotic cells (Liu et al, 2016, 2017), and are found even in plant RNA viruses and plant tumors. They have potent biological activities.…”
Section: Distribution and Metabolism Of Pas In Plantsmentioning
confidence: 99%
“…Polyamines (PAs) are low molecular weight aliphatic nitrogenous bases containing two or more amino groups, and they have potent biological activity (Xu et al, 2009; Vuosku et al, 2018). They are widely distributed in eukaryotic and prokaryotic cells (Liu et al, 2017; Mustafavi et al, 2018). In living organisms, PAs mainly exist in free (F-PAs), covalently conjugated (CC-PAs) or non-covalently conjugated (NCC-PAs) forms (Gholami et al, 2013).…”
Section: Introductionmentioning
confidence: 99%